Investigation on the limp properties of formed foils for hydrogen applications - Wituschek, Simon; Römisch, David; Lechner, Michael; Merklein, Marion (IOP Conference Series: Materials Science and Engineering, 2024)
The mass production of bipolar plates for electrolyzers and fuel cells is a central step towards the realization of efficient and cost-effective energy systems of the future. However, current production processes are reaching their limits and can hardly realize the quantities that will soon be demanded, nor can they scale up to the required volumes. Particularly for the handling of half-plates and bipolar plates, major challenges are to be expected, especially with regard to production rates. Existing handling systems have restricted scalability and precision. Therefore, new stacking technologies are necessary, which have to be adaptable to the mechanical properties of the components and maintain tight tolerances during stacking to ensure hydrogen sealing for safety and efficiency. An important property in the handling of the plates is their limpness, which is distinguished by instability of the components as well as plastic deformation at low forces and moments. Therefore, the limp behavior of the components must be analyzed. To investigate the limpness of foil components, a flowfield is first formed using a 1.4404 stainless steel foil with a sheet thickness of 0.075 mm. Subsequently, the workpieces are analyzed in terms of their limp properties by means of a 3-point bending test.<br